The Effect Of Current Ratio, Debt To Equity Ratio, Debt To Asset Ratio And Time Interest Earned Ratio On Profit Growth at PT Aneka Tambang tbk - sarfiah, sarfiah; Rimawan, M. (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
This study is anssociative studyat that at aims to determine the effect of current ratio, debt to equity ratio, debt to Asset Rasio and Time Interest Earned Ratio on profit grown at PT. Aneka Tambang Tbk. This study uses financial reports with a population of 20 year and the sample used is 9 years. The date collection techniquens used in this study are documentation and literature study. The data analysis technique used is multiple linear regression test, namely the statistical method of classical assumption test multicollinearity heteroscedasticity multiple linear regression t test f test and coefficien of determination. The research result is There is no influence of Current Ratio, Debt to Equity Ratio, Det to Asset Ratio, and Time Interest Earned Ratio to profit growth at PT Aneka Tambang Tbk